2012
DOI: 10.1111/j.1365-2761.2012.01393.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Aquaflor®, copper sulphate and potassium permanganate for control of Aeromonas hydrophila and Flavobacterium columnare infection in sunshine bass, Morone chrysops female × Morone saxatilis male

Abstract: Two experiments were conducted to test the effectiveness of different therapeutants against a mixed infection of Aeromonas hydrophila and Flavobacterium columnare in sunshine bass. Experiment 1 evaluated copper sulphate, florfenicol‐medicated feed and potassium permanganate (KMnO4) against a natural mixed infection. Experiment 2 further evaluated copper sulphate as a treatment to control an experimental mixed infection. In experiment 1, naturally infected untreated fish had the lowest final survival per cent, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Darwish et al (2012) evaluated the efficacy of different therapeutants in HSB exposed to a mixed infection of Aeromonas hydrophila and F. columnare during both natural and experimental infections. In a study to evaluate the im munocompetency of HSB fed test diets with varying levels of vitamin E, Trushenski & Kohler (2008) reported an incidental F. columnare outbreak in test fish, which was presumably a contaminant in a stock culture of Streptococcus iniae, the intended pathogen to be tested.…”
Section: Discussionmentioning
confidence: 99%
“…Darwish et al (2012) evaluated the efficacy of different therapeutants in HSB exposed to a mixed infection of Aeromonas hydrophila and F. columnare during both natural and experimental infections. In a study to evaluate the im munocompetency of HSB fed test diets with varying levels of vitamin E, Trushenski & Kohler (2008) reported an incidental F. columnare outbreak in test fish, which was presumably a contaminant in a stock culture of Streptococcus iniae, the intended pathogen to be tested.…”
Section: Discussionmentioning
confidence: 99%
“…Different media were used to cultivate the bacteria, including Hsu-Shotts or modified Hsu-Shotts medium [79,114], Ordal’s medium [115], Anacker and Ordal’s medium also referred to as “Cytophaga medium” [94], F. columnare growth medium broth [115] and Shieh or modified Shieh medium [12,23,43-45,105]. The bacteria were mostly grown on a shaker [43-45,75,109-111].…”
Section: Experimental Trials/pathogenicity Testsmentioning
confidence: 99%
“…Gaunt et al demonstrated the efficacy of florfenicol in the feed against columnaris disease in channel catfish [136]. Darwish et al also illustrated the clear benefit of florfenicol against a mixed infection of A. hydrophila and F. columnare in Sunshine bass (hybrid striped bass, Morone chrysops female × Morone saxatilis male) [115]. The excessive use of antimicrobial agents to withstand F. columnare has its negative attributes though [20].…”
Section: Controlmentioning
confidence: 99%
“…Analysis revealed the presence of efflux and response elements conferring resistance to copper, lead, cadmium, and zinc in all three genomes. Since the exposure of fish to copper sulfate solution is one of the treatments used against F. psychrophilum infection ( 8 ), the presence of these resistance elements in these outbreak-causing strains might be conferring resistance. Genes conferring resistance to fluoroquinolones and beta-lactam antibiotics were also detected in all three genomes.…”
Section: Genome Announcementmentioning
confidence: 99%